The concept of the impact of market orientation on company performance - Dąbrowski, Dariusz (Journal of Management and Financial Sciences, 2025)
The current explanation of the impact of market orientation on company performance is based on the search for competitive advantage, understood as offering the greatest value to customers. However, the development of economic thought has led to the understanding that it is the economic value that a company creates through its product that forms the basis for gaining competitive advantage. Therefore, it was deemed necessary to revise the mechanism of how market orientation affects company performance, aiming to develop a conceptual model of this impact. To achieve this goal, a substantive analysis of the phenomenon under study was performed. The result of the work is a model indicating that the impact of market orientation on company performance is complex, as it involves mediating factors such as benefits perceived by customers from using the product, product costs, economic value, and customer surplus.